Testing the general validity of the Heckscher-Ohlin theorem: The natural experiment of Japan - Daniel M. Bernhofen; John C. Brown (Center for Economic Studies and ifo Institute (CESifo), 2011)
We exploit Japan's 19th century move from autarky to free trade to provide the first test of the general validity of the price formulation of the Heckscher-Ohlin theorem. In this formulation a country's autarky factor price vector imposes a single refutable prediction on the economy's factor content of trade. Our test combines factor price data from Japan's late autarky period with Japan's factor content of trade calculated with the technologies of the country of origin of traded goods. The direct and indirect input requirements are constructed from many historical sources, including a major Japanese survey of agricultural techniques and a rich set of 19th century comparative cost studies. Evaluating Japan's factor content of trade during 1865-1876 at autarky factor prices, we fail to reject the Heckscher-Ohlin hypothesis in each sample year.
Keywords: F11; F14; N10; N75; 330; testing the price version of Heckscher-Ohlin; the natural experiment of Japan